2019
DOI: 10.1088/1741-2552/aaed17
|View full text |Cite
|
Sign up to set email alerts
|

Tracking feature-based attention

Abstract: Objective. Feature-based attention (FBA) helps one detect objects with a particular color, motion, or orientation. FBA works globally; the attended feature is enhanced at all positions in the visual field. This global property of FBA lets one use stimuli presented in the peripheral visual field to track attention in a task presented centrally. The present study explores the use of SSVEPs, generated by flicker presented peripherally, to track attention in a visual search task presented centrally. We evaluate wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 62 publications
0
12
0
1
Order By: Relevance
“…这些发现引领了随后一系 列的研究 [63~65] . 有趣的是, 最近研究发现, 在虚拟的三 维空间中进行基于特征的目标搜索时, 空间注意焦点 之外的目标特征也有更高的SSVEP的激活 [66] . 可以说,…”
Section: 叠加理论认为 稳态脑电反应是一系列瞬态Erp的unclassified
“…这些发现引领了随后一系 列的研究 [63~65] . 有趣的是, 最近研究发现, 在虚拟的三 维空间中进行基于特征的目标搜索时, 空间注意焦点 之外的目标特征也有更高的SSVEP的激活 [66] . 可以说,…”
Section: 叠加理论认为 稳态脑电反应是一系列瞬态Erp的unclassified
“…Finally, in the central task with peripheral flicker (Appendix S), participants performed a task near fixation (e.g., visual search), and feature-based attention was measured indirectly via a peripheral flickering stimulus (i.e., this design took advantage of the spatially global spread of feature-based attention; White & Carrasco, 2011;Sàenz, Buraĉas, & Boynton, 2002. Studies using a central task with peripheral flicker include Chu and D'Zmura (2019); Jiang, Wu, and Gao (2017);Painter, Dux, and Mattingley (2015); and Painter, Dux, Travis, and Mattingley (2014).…”
Section: Task Used In Each Studymentioning
confidence: 99%
“…Although some studies have argued that feature-based attention effects do not qualitatively appear to vary with frequency (Steinhauser & Andersen, 2019;, the vast majority of reviewed studies only reported statistical significance of an overall attention effect collapsed across frequencies. Only a handful of studies have reported statistical significance of individual frequencies (e.g., Chu & D'Zmura, 2019;Steinhauser & Andersen, 2019;Painter et al, 2014;Quigley & Müller, 2014). As such, future work is needed to systematically investigate the effect of frequency choice on feature-based attention effects, particularly for frequencies > 20 Hz.…”
Section: Ssvep Frequenciesmentioning
confidence: 99%
“…Studies using a hemi-field flicker task include: (Adamian et al, 2019;Andersen et al, 2013;Andersen, Fuchs, et al, 2011;Störmer & Alvarez, 2014) Finally, in the central task with peripheral flicker, participants performed a task near fixation (e.g., visual search), and feature-based attention was measured indirectly via a peripheral flickering stimulus (i.e., this design took advantage of the spatially global spread of feature-based attention, Sàenz et al, 2002Sàenz et al, , 2003White & Carrasco, 2011). Studies using a central task with peripheral flicker include: (Chu & D'Zmura, 2019;Jiang et al, 2017;Painter et al, 2014Painter et al, , 2015.…”
Section: Focused Review Of Feature-based Attention Studies Using Ssvepsmentioning
confidence: 99%
“…Although some studies have argued that feature-based attention effects do not qualitatively appear to vary with frequency Steinhauser & Andersen, 2019), the vast majority of reviewed studies only reported statistical significance of an overall attention effect collapsed across frequencies. Only a handful studies have reported statistical significance of individual frequencies (e.g., Chu & D'Zmura, 2019;Painter et al, 2014;Quigley & Müller, 2014;Steinhauser & Andersen, 2019). As such, future work is needed to systematically investigate the effect of frequency choice on feature-based attention effects, particularly for frequencies >20 Hz.…”
Section: Ssvep Frequenciesmentioning
confidence: 99%